2020
DOI: 10.3389/fmicb.2020.577756
|View full text |Cite
|
Sign up to set email alerts
|

Forward Genetics Reveals a gatC-gatA Fusion Polypeptide Causes Mistranslation and Rifampicin Tolerance in Mycobacterium smegmatis

Abstract: Most bacteria, including mycobacteria, utilize a two-step indirect tRNA aminoacylation pathway to generate correctly aminoacylated glutaminyl and asparaginyl tRNAs. This involves an initial step in which a non-discriminatory aminoacyl tRNA synthetase misacylates the tRNA, followed by a second step in which the essential amidotransferase, GatCAB, amidates the misacylated tRNA to its correct, cognate form. It had been previously demonstrated that mutations in gatA can mediate increased error rates specifically o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…We had previously identified via forward genetic screens strains of Mycobacterium smegmatis with extremely high specific rates of mistranslation due to mutations in the essential amidotransferase genes gatCAB (Cai et al, 2020; Su et al, 2016). We hypothesized that the mycobacterial genome may encode for other ‘fidelity factors’ that may either enhance or reduce mistranslation specifically involving the indirect tRNA aminoacylation pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We had previously identified via forward genetic screens strains of Mycobacterium smegmatis with extremely high specific rates of mistranslation due to mutations in the essential amidotransferase genes gatCAB (Cai et al, 2020; Su et al, 2016). We hypothesized that the mycobacterial genome may encode for other ‘fidelity factors’ that may either enhance or reduce mistranslation specifically involving the indirect tRNA aminoacylation pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we sought to identify further translational fidelity factors in mycobacteria, which we had previously shown have high, but specific rates of mistranslation due to the indirect tRNA aminoacylation pathway required for aminoacylation of glutaminyl- and asparaginyl-tRNAs (Cai et al, 2020; Chaudhuri et al, 2018; Su et al, 2016). Our screen identified loss-of-function mutations in gidB conferring increased fidelity to errors generated by mutants in this pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of these mutations concentrated in the range of 5%-10%, and they were predominantly found in genes whose encoded proteins are involved in cell wall and cell processes, intermediary metabolism and respiration (Figure 2B). When the genes carrying unfixed mutations were ranked according to the significance of the mutations' association with poor outcomes, the highest ranked gene was gatA, which has been associated with rifampicin tolerance (Cai et al, 2020) (Figure 2C). Gene expression patterns under stress conditions can provide important insights into the function of the gene (Bosch et al, 2021).…”
Section: Identification Of a Functional Mutation Set For Predicting T...mentioning
confidence: 99%
“…Su et al found that M. smegmatis experiences increased levels of mistranslation with reduced activity of GatCAB, which is an enzyme that transamidates glutamine and asparagine tRNAs that had been improperly acylated with glutamate and aspartate, respectively [111]. Strains of M. smegmatis with lower GatCAB activity not only exhibited high levels of mistranslation but also high rates of phenotypic resistance to rifampicin [117]. Further analysis revealed that rifampicin phenotypic resistance was lower in strains where residue 434 of RpoB, which is normally an asparagine, was changed to a threonine [111].…”
Section: Phenotypic Resistance Mechanismsmentioning
confidence: 99%